The 2021 European Union report on pesticide residues in food - European Food Safety Authority (EFSA); Luis Carrasco Cabrera; Giulio Di Piazza; Bruno Dujardin; Paula Medina Pastor (EFSA Journal)
Abstract Under European Union legislation (Article 32, Regulation (EC) No 396/2005), EFSA is to provide an annual report assessing the pesticide residue levels in foods on the European market. In 2021, 96.1% of the overall 87,863 samples analysed fell below the maximum residue level (MRL), 3.9% exceeded this level, of which 2.5% were non‐compliant, i.e. samples exceeding the MRL after accounting for the measurement uncertainty. For the EU‐coordinated multiannual control programme subset, 13,845 samples were analysed of which 2.1% exceeded the MRL and 1.3% were non‐compliant. To assess acute and chronic risk to consumer health, dietary exposure to pesticide residues was estimated and compared with available health‐based guidance values (HBGVs). A new pilot methodology based on probabilistic assessment was introduced to provide the probability of subjects being expose to an exceedance of the HBGV. Recommendations to risk manager are given to increase the effectiveness of European control systems and to ensure a high level of consumer protection throughout the EU.